Juegos tradicionales y su influencia en el desarrollo de las capacidades motrices de los estudiantes de primero y segundo año de educación básica de la Unidad Educativa Caracol, Parroquia Caracol, Cantón Babahoyo Provincia de los Ríos en el año 2016 - Cabezas Valverde, Tatiana (2016)
The research is entitled "Traditional Games and their influence on the development of motor skills of freshmen and sophomores of Basic Education of the Education Unit Caracol, parish Caracol, Canton Babahoyo province of the Rivers in the academic year 2015 -2016 "is a current theme, because it is directed towards finding solutions, useful not only for schools but for life in general. To comply with planned objectives were used methods of scientific research, theoretical and empirical levels, as well as mathematical and statistical methods that were used in the processing of data derived from the application of technical scheduled. Is the opinion of this author that take into account scientific result obtained by the relevant authorities, this `could impartar significantly in the methodological training of teachers, thus promoting an improvement in the pedagogical direction of teaching - learning plans